Impact of COVID-19 on Gender-Based Violence Prevention and Response Services in Kenya, Uganda, Nigeria, and South Africa: A Cross-Sectional Survey - Roy, Charlotte M.; Bukuluki, Paul; Casey, Sara E.; Jagun, Moriam O.; John, Neetu A.; Mabhena, Nicoletta; Mwangi, Mary; McGovern, Terry (Frontiers in Global Women's Health, 2022)
Background Epidemics and other complex emergencies historically have had a disproportionate impact on women and girls, increasing their vulnerability to gender-based violence (GBV). The COVID-19 pandemic has been no different, with reports of rising cases of GBV emerging worldwide. Already a significant problem in Kenya, Uganda, Nigeria, and South Africa, GBV in these countries has been exacerbated by government restrictions intended to contain the spread of COVID-19. The purpose of this study was to understand how the COVID-19 pandemic affected the availability of GBV prevention and response services from the perspective of the organizations that provide them. Methods A cross-sectional online survey of people who work in GBV prevention and response in Kenya, Uganda, Nigeria, and South Africa was administered from July to October 2020. A convenience sample was identified through web search, contacts of in-country consultants, and relevant listservs and technical working groups. Descriptive analyses were completed using SPSS. Results A total of 187 respondents completed the survey. Nearly all (98.9%) survey respondents reported that COVID-19 impacted their work. The majority (77.9%) stated that work decreased due to government restrictions or GBV services being deemed non-essential. The types of service most impacted were community-based prevention, shelters, and legal services. Survey respondents overwhelmingly agreed (99.3%) that COVID-19 impacted GBV prevalence and identified adolescents and women with disabilities as particularly vulnerable groups. Conclusions GBV prevention and response services in Kenya, Uganda, Nigeria, and South Africa were highly impacted by the COVID-19 pandemic, largely due to government restrictions and the failure of governments to deem GBV services as essential. Preparedness for future crises should ensure that GBV is adequately prioritized in the initial response in order to maintain service availability with special attention paid to at-risk populations.